HIV sero-status disclosure and associated factors among HIV positive women in East Africa: Systematic review and meta-analysis. Implications for prevention of mother-to-child HIV transmission - Mosisa, Getu; Mulisa, Diriba; Oluma, Adugna; Bayisa, Lami; Merdassa, Emiru; Bayisa, Diriba; Tamiru, Afework; Tolossa, Tadesse; Chala Diriba, Dereje; Fetensa, Getahun; Wakuma, Bizuneh (Frontiers in Public Health, 2022)
Abstract Background: Women’s HIV-positive disclosure plays a pivotal role to achieve the goal of preventing mother-to-child transmission (PMTCT) among pregnant women in particular. Although several primary studies were conducted in the different countries of East Africa, no study concluded the prevalence of women’s HIV status disclosure and associated factors in East Africa. Therefore, the current study aimed to assess the pooled prevalence of disclosure status and associated factors among women in East Africa. Objectives: To assess pooled prevalence of HIV sero-status disclosure and associated factors among women in the East Africa. Methods: HINARI, PubMed, and Cochrane Library databases were searched. The data were extracted using a Microsoft Excel spreadsheet and STATA 14.1 version was used for analysis. The Funnel plots and Egger’s statistical test was used to check publication bias. Heterogeneity was assessed by conducting sensitivity and subgroup analyses. Result: The pooled prevalence of serostatus disclosure among women in East Africa was 73.77% (95%CI 67.76, 79.77). Knowing partner’s serostatus (OR=10.04(95%CI 3.36, 31.84), married (OR=2.46 (95%CI 1.23, 4.89), smooth relationship (OR=3.30 (95%CI 1.39, 7.84), and discussion on HIV before the test (OR=6.96 (95%CI 3.21, 15.05) were identified determinants of HIV serostatus disclosure. Conclusion: The current systematic and meta-analysis revealed that nearly one-fourth of women hadn’t disclosed HIV serostatus to at least one individual. Knowing the partner’s HIV serostatus, being married, having a smooth relationship, and discussing on HIV before the test were determinants of disclosure status. Therefore, disclosure of HIV-positive serostatus among women living with HIV needs to be strengthened.